COMPARATIVE EFFICACY OF OVSYNCH AND OVSYNCH+CIDR IN POST-PARTUM ANOESTRUS BUFFALOES - KUMAR M, PRAVEEN; BRAMHAIAH K, VEERA; MUTHARAO, M (The Indian Journal of Animal Reproduction, 2022)
Synchronization of post-partum anoestrus buffaloes with ovsynch and ovsynch+CIDR showed that theestrus response, time taken for onset of estrus and duration of estruswere 71.43 and 71.43 %; 62.4±1.21 and 57.25±1.25 h and 18.80±0.66 and 20.25±1.75 h, respectively and its differencebetween protocols did not show any significant difference.The mean serum progesterone concentrations on different days of synchronization viz., on treatment initiation day, at the time of PGF2 administration and on the day of AI were 0.74±0.50 and 0.01±0.01; 3.54±0.47and 4.33±0.74and 1.17±0.47 and 0.95±0.74 ng/ml, respectively and its concentration difference between protocols was not significant (P>0.05) and within each protocol was significant (P<0.05).Resumption of ovarian activity and development of functional dominant follicle at synchronized estruswas good with Ovsynch+CIDR with overall conception rate of 71.43%. While the same was 57.14%with Ovsynch protocol.